Evaluation of the Marketing Strategy of Mama Zila Pasuruan Spinach Stick MSME in Enhancing Product Competitiveness - M. Asif Nur Fauzi; Jazilatur Rohmah; Nuruddin; Ali Machrus; Chulil Barory (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
The increasingly competitive snack food industry demands that Micro, Small, and Medium Enterprises (MSMEs) employ adaptive and innovative marketing strategies to maintain their existence and enhance product competitiveness. This study aims to evaluate the marketing strategy implemented by Mama Zila's Stick Bayam MSME and analyze its impact on product competitiveness. This study employed a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the marketing strategy implemented is still traditional, including products made from natural ingredients without preservatives, affordable prices, limited direct distribution, and promotion only through word of mouth and personal social media. Business evaluation was conducted informally through consumer feedback and manual sales recording. Follow-up actions from the evaluation results included packaging improvements, PIRT permit processing, digital promotion training, periodic financial records, and responses to customer feedback. Although simple, the strategy and evaluation conducted show the potential to increase product competitiveness if accompanied by strengthening branding, developing distribution, and maximizing digital technology utilization.